Effect of Vitamin C Exposure to Fibroblast Cells on Woman Uterosacral Ligament Culture - Rahajeng Rahajeng; Tatit Nurseta; Edy Mustofa; Yahya Irwanto; Aditiya Fendi Uji Pamungkas; Dhian Eka Putri Harnandari; Putu Arik Herliawati (Medical Laboratory Technology Journal, 2023)
Pelvic Organ Prolapse (POP) occurs when the uterosacral ligaments weaken. Vitamin C plays a major role in forming the extracellular matrix (collagen) and stimulates fibroblast cell proliferation. This study aimed to examine how a woman's uterosacral ligament culture was affected by vitamin C exposure to fibroblast cells. A straightforward experimental design investigation that is non-blind and includes analysis after exposure (Post-test control group design). This study's sample used uterosacral ligament from a woman who underwent at least two vaginal deliveries through a hysterectomy procedure. Several doses of vitamin C were given and repeated for 72 hours, followed by examining the number of fibroblast cells; then, the data was analyzed starting with the parametric prerequisite test and the one-way ANOVA test. There was a significant effect of vitamin C exposure on fibroblast cells of the uterosacral ligament at a dose of 50 μg/ml and 100 μg/ml. In contrast, at doses of 150 μg/ml and 200 μg/ml, there was no significant effect. From this study, it is hoped that the administration of vitamin C according to the optimal dose found in the study (significant impact at doses of 50 μg/ml and 100 μg/ml, can increase the proliferation of fibroblast matrix supporting the sacrouterine ligament in women, to prevent prolapse of the pelvic organs in women, and can maintain the quality of life of women.